Determination of perception-reaction time of Thai motorcyclists for stopping sight distance using a driving simulator - Thapa, Neelam; Kunnawee Kanitpong; Surachet Pravinvongvuth; Ampol Karoonsoontawong; Asian Development Bank - Japan Scholarship Program (ADB-JSP) (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
Perception Reaction Time of a driver is a very fundamental criteria adopted for design of highway. The 2.5 seconds perception reaction time value used by American Association of State Highway and Transportation Officials (AASHTO) is derived using a passenger car which is considered as the design vehicle. However, in countries like Thailand where the motorcycle representation in the traffic is so strong yet motorcycle safety is in very worrying state, steps should be undertaken to ensure motorcycle safety. One of the most effective engineering interventions to promote motorcycle safety would be segregation of motorcycle from other heterogenous vehicle by construction of exclusive motorcycle lane. At the same time, it is crucial to understand how different the perception reaction time value of motorist is as compared to passenger car driver whose value would then govern the different elements of design of exclusive motorcycle lane. This study aims to determine the perception reaction time (PRT) of motorcyclist using a driving simulator. 68 participants performed the tests in driving simulator where they applied brake for stopping as soon as the graphic circle turn from grey to red i.e. in expected condition. The mean PRT value is 0.625 seconds while 85th percentile value is 1.005 seconds. Also, the different factors relating to riders like gender, age, riding experience and riding frequency on the perception reaction time value was analyzed using multiple linear regression model. Additionally, the braking maneuver (method of brake application) of the participants as well as their subsequent effect on braking distance were studied combining the participants respond using questionnaire survey as well as results from riding simulator.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Transportation Engineering
Thesis (M.Sc.) - Asian Institute of Technology, 2020
Keywords: Motorcyclists -- Thailand; Traffic safety -- Thailand; Roads -- Visibility